2018
DOI: 10.1039/c8ta00356d
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio study for probing iodization reactions on metallic anode surfaces of Li–I2 batteries

Abstract: A Li oxynitride protecting layer produced by the LiNO3 additive can prohibit surface iodization and LiI exfoliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…bond length of the outcast I 2 molecule is 2.86 Å, which is only 0.2 Å longer than that of the free I 2 molecule. 53 Figure 6a shows the net charge variation of I atoms repulsed by the substrate. At 0.15 ps, both of them are charged by −0.5|e| because they are near to the Mg surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bond length of the outcast I 2 molecule is 2.86 Å, which is only 0.2 Å longer than that of the free I 2 molecule. 53 Figure 6a shows the net charge variation of I atoms repulsed by the substrate. At 0.15 ps, both of them are charged by −0.5|e| because they are near to the Mg surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous theoretical and experimental studies have demonstrated that LiNO 3 additive can protect the metallic Li anode in Li−S batteries 62−64 and Li−I 2 batteries. 53,65 Inspired by these efforts, the present study also evaluates Mg(NO 3 ) 2 as the electrolyte additive for protecting the Mg(0001) surface. Our AIMD simulation demonstrates that Mg(NO 3 ) 2 can be reduced by the Mg surface and form a thin magnesium oxynitride layer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, the dissolved iodine species will uncontrollably shuttle to the anode and react with the anode, causing low Coulombic efficiency, severe self‐discharge, and a short cycling life. [ 47,48 ]…”
Section: Operational Mechanisms and Shuttle Effect Of Novel Esssmentioning
confidence: 99%
“…Lithium metal surface is known to be active and is prone to react with the small gas molecules present in its environment [47,48] . Zavadil and Armstrong have made significant contribution to explore the chemistry of small molecules on lithium surface [49,50] .…”
Section: Introductionmentioning
confidence: 99%
“…[46] Lithium metal surface is known to be active and is prone to react with the small gas molecules present in its environment. [47,48] Zavadil and Armstrong have made significant contribution to explore the chemistry of small molecules on lithium surface. [49,50] The work carried out to determine the rate of passivation of lithium metal with the exposure of environmental gases clearly advocates the high susceptibility of lithium towards these gases.…”
Section: Introductionmentioning
confidence: 99%